GAMBARAN PENERAPAN STANDAR OPERASIONAL PROSEDUR PERAWATAN LUKA PADA POST OPERASI FRAKTUR FEMUR TERTUTUP DI RUMAH SAKIT SANTA ELISABETH MEDAN TAHUN 2017 - Sardo Hot Roganda Sinaga; Magda Siringoringo (STIKes Santa Elisabeth Medan, 2017)
Standard operating procedure (SOP) is the guide to start or to do some jobs, where is the place to do, what should they do and how they can do it. The patient in post operation facture close femur is one of category that should apply in keeping patient or injuring them in correct way. Keeping the wound in correct way is the basic step to injure the patient in sterile that follow procedure. The aim is to help the patient to get curing as soon as possible from the wound. Goal: : The aim from this case study is to see how they apply their knowledge to keep the patient for injuring in post operation facture close femur in Santa Elisabeth hospital Medan 2017. Methods: Case study method that may apply in here is Descriptive. The population is about 12 respondents, the instrument of this research is using post operation and the result will get by Univariate analysis. Result: From univariate analysis the result could divide into two categories these are good application is about 83,3% and enough application is about 16,7%. Conclusion: From the case study in The General implementation figure of standard operational keeping care for injuring in post operation facture close femur in Santa Elisabeth hospital Medan 2017, the result is good. And hopefully this procedure will keep in long time and give the best service to make the patient feel good as well as they get the appropriate procedure.